Pembagian Harta Bersama Dalam Perkawinan Keluarga Muslim - Oyo Sunaryo Mukhlas; Nasrudin (STAI Siliwangi Bandung, 2015)
Legal values ​​that live in the community, including customs are having very big influence on the formation of the formulation of joint property as stipulated in article 85 to article 97 Compilation of Islamic Law. The formulation of joint property was carried out through the approach path syirkah Abdan rules and customs. The formulation of joint property or the more viscous is also called the treasure-rich mixed-rajakaya that can occur when a person is bound by marriage. With matrimony, then the income will be shifted according to attach obligations and rights as husband and wife. Wife’s Income unanimously regarded as the property of origin, because the wife is not burdened with providing for her husband. However, upon mutual agreement, especially the wife sincerity and husband’s permit, the wife can be a partner/companion in making a living. While the husband’s income is a capital property to make a living for his family, because the husband obligated to provide including for his wife. Thus, the formalization of joint property arrangements in marriage law in Indonesia was essentially aims to provide a balanced appreciation (proportional) to the conjugal cooperation in building and maintaining the household. If the judges in deciding section treasure together for the widower and divorcee living using Abdan syirkah rules and customary law, as well as methods of discretion, or ijtihad with the approach of the rules istinmbat al Ahkam, not a violation of law, it can even be appreciated as a progressive legal invention. Given the essential meaning of the provisions of Article 97 KHI is set (degelen) is not forcing (dwigen).